Unstable crack propagation in LAPONITE® gels: selection of a sinusoidal mode in an electric field. Issue 69 (6th July 2016) - Hazra, Somasri; Sircar, Sudeshna; Khatun, Tajkera; Choudhury, Moutushi Dutta; Giri, Abhra; Karmakar, Sanat; Dutta, Tapati; Das, Shantanu; Tarafdar, Sujata
Abstract : We report observation of wavy cracks and naturally patterned fracture surfaces in drying LAPONITE® paste. Abstract : We report observation of wavy cracks and naturally patterned fracture surfaces in drying LAPONITE® paste. Desiccation cracks are shown to follow undulating, corrugated paths even when the speed of crack propagation is lower than the sound velocity in the medium by two orders of magnitude. Fast Fourier transform of the wavy crack path shows that it is a superposition of several sinusoidal modes and their harmonics. When the paste is exposed to a DC electric field during drying, by imposing a 50 V potential, some of the modes are suppressed. Increasing the voltage to 100 V results in survival of only one pure sinusoidal mode of wavelength ∼292 μm. We suggest that an effective mixed mode loading develops as a result of faster evaporation at the upper surface of the paste, and this is responsible for the instability leading to the wavy contour of the crack. The present study provides an insight into the mechanism of wavelength selection under an electric field of sufficient strength. We also show that unstable crack propagation may have similarity with the mechanism that exists in an auxiliary experiment: breaking of a perspex sheet.